Feasibility and reliability of sentinel lymph node biopsy after neoadjuvant chemotherapy in breast cancer patients with positive axillary nodes at initial diagnosis: An up-to-date meta-analysis of 3, 578 patients. (October 2021) - Cao, Siyang; Liu, Xia; Cui, Junwei; Liu, Xiaoling; Zhong, Jieyu; Yang, Zijian; Sun, Desheng; Wei, Wei
Abstract: Purpose: Neoadjuvant chemotherapy (NACT) is increasingly adopted in the therapy of breast cancer (BC) patients with positive axillary nodes (cN+), but the reliability and feasibility of sentinel lymph node biopsy (SLNB) following NACT are still controversial. The objective of the present study is to conduct an updated meta-analysis on this issue. Methods: A literature search was performed using PubMed, Cochrane, Embase, and Web of Science to identify papers published from January 1, 2000 to October 22, 2020 to research SLNB after NACT in BC patients. Studies that met the quality standard were enrolled for this meta-analysis. Results: A total of 3578 participants from 27 trials were included in this meta-analysis. The pooled estimate of the identification rate (IR) for SLNB was 91 %, and the false negative rate (FNR) was 15 %. The pooled negative prediction value (NPV), accuracy, specificity, and sensitivity were 82 %, 89 %, 97 %, and 85 %, respectively. In subgroup analysis, the application of dual mapping could clearly decrease the FNR. The FNR was significantly high in the luminal types, and it declined as more sentinel lymph nodes (SLNs) were removed. Conclusion: SLNB following NACT is now technically feasible for BC with cN+. However, it must be emphasized that the FNR is unacceptable high. Highlights: We performed a meta-analysis to provide a consensus regarding the application of SLNB post-NACT in cN + patients. One comprehensive database search yielded 27 studies (3578 patients). The pooled estimate of IR for SLNB was 91 %, and FNR was 15 %. The application of dual mapping could clearly decrease the FNR.